Adaptation of students with disabilities in Special Schools during the Covid-19 pandemic - Mawardi, Rafi Aufa; Budirahayu, Tuti (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
The Covid-19 pandemic has had negative implications for the education sector, including Special Schools. This study was conducted to analyze formal pedagogical practices in Special Schools and the adaptations made by students with disabilities during the Covid-19 pandemic. This study was conducted using qualitative research methods and a phenomenological approach. Robert K. Merton's adaptation theory is used to analyze the types of adaptations made by students with disabilities to formal pedagogical practices during the Covid-19 pandemic. This study finds that the Covid-19 pandemic reproduces formal pedagogical practices in two formats, namely online and hybrid. Apart from that, the form of adaptation of students with disabilities is largely determined by their physical, cognitive, and mental conditions. Among them are students with intellectual disabilities who have the innovation adaptation type, then students with deaf-speech impairments who have the conformity adaptation type, and students with autism have the ritualism adaptation type. This type of adaptation reflects the dynamics and complexity of students with disabilities when carrying out the learning process during the Covid-19 pandemic.